Learning Design of Quadratic Equation Using ICT to Understand the Concept and Reduce Math Anxiety - Nasution, Syaiful Hamzah; Jupri, Al (Universitas Teknokrat Indonesia, 2025)
Quadratic equations are essential material that students need to master. Based on several studies, many students have not mastered the material because they have not mastered the prerequisite skills and find solutions. This study aims to describe the learning design of quadratic equations using ICT, namely the Algebra Tile app, to understand the concept and reduce students' math anxiety regarding Cone of Experience Theory, Information Processing Theory, and Genesis Instrumentation Theory. The material is limited to quadratic equations with rational roots. The design of learning quadratic equations using ICT refers to three stages of development, namely: (1) analysis stage, (2) design stage, and (3) development stage. The results showed that the learning design was valid, practical, and effective. Using algebraic tile applets helped students factor in quadratic equations and lowered their anxiety during learning. Furthermore, the efforts made by the teacher by dividing students into several groups during learning, providing learning videos, ice breaking, and a short pause after conveying the concept can reduce students' anxiety.